Analisis Sistem Antrian dalam Meningkatkan Efektivitas Pelayanan Menggunakan Metode Accidental Sampling - Rakhmad Pribowo Hariputra; Sarjon Defit; Sumijan (Jurnal Sistim Informasi dan Teknologi, 2022)
Queue is a process of waiting to be served if a service facility (server) is still busy. After getting service, the queue is left to get service facilities. One of the busy places of service and the existence of services is the Solok City Hospital. Services at the hospital always have a queuing process. This process starts from registration to completion, namely making payments at the cashier. Currently, mobile media has become one of the important aspects in supporting queue services. Technological advances that use mobile media have provided many advantages and conveniences in saving time and reducing the number of workers and costs in service. One method of improving services with mobile media is the Accidental Sampling method. This method is very effective in using queue time. So this research was carried out to improve hospital services so that visitors and the hospital could save time in getting services and serving. The data processed in this study was carried out in 30 days with measurements using the calculation of the probability of no visitors, the average number of visitors, the average number of visitors waiting in the queue, and the average time waiting in line. The result of this study is to add 1 waiter per counter, so the optimal time to overcome the queue at the hospital. So that this research can be used as a reference in improving services to overcome the problem of queuing visitors